PENGUATAN KEARIFAN LOKAL DALAM PIMILIHAN KEPALA DESA - Muhammad Ruhly Kesuma Dinata; Ibrahim Fikma Edrisy (Universitas Gorontalo, 2022)
the issuance of Law No. 06 of 2014 concerning Villages, villages get better attention from the central government and local governments because there is a village fund policy from the central government to finance village community development and empowerment worth hundreds of millions plus the Village Fund Allocation from the Regional Government for finance the administration of government, implementation of development, community development and empowerment of rural communities worth tens of millions. The size of the budget obtained by the village makes the election of the village head more attractive.In North Lampung, there are 141 villages that will conduct village head elections simultaneously and 463 Village Head Election Participants. In Law No. 6 of 2014 concerning villages, the administration of village government is in accordance with the characteristics, culture and local wisdom of each region. However, at the stages of village head elections, problems arise that are not in accordance with local wisdom in North Lampung, such as indications of alleged violations of money politics, persecution perpetrated by one of the candidates for village head